2016
DOI: 10.3390/rs8010057
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Melt Ponds on Arctic Multiyear Sea Ice in Summer from TerraSAR-X Dual-Polarization Data Using Machine Learning Approaches: A Case Study in the Chukchi Sea with Mid-Incidence Angle Data

Abstract: Melt ponds, a common feature on Arctic sea ice, absorb most of the incoming solar radiation and have a large effect on the melting rate of sea ice, which significantly influences climate change. Therefore, it is very important to monitor melt ponds in order to better understand the sea ice-climate interaction. In this study, melt pond retrieval models were developed using the TerraSAR-X dual-polarization synthetic aperture radar (SAR) data with mid-incidence angle obtained in a summer multiyear sea ice area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 83 publications
(119 reference statements)
3
44
1
Order By: Relevance
“…The lack of backscatter from the melt pond surfaces compared to the sea ice could potentially be used for f MP retrieval utilising σ 0 , as the backscatter intensity becomes weaker with increasing f MP . This is confirmed by Han et al (2016), suggesting σ 0 to be a key feature in f MP estimation for MYI in X-band during calm winds. On the other hand, our results deviate from findings in C-band, where no correlation was found between σ 0 HH and f MP at low wind speeds (U 10 = 1.5 m s −1 ) by Yackel and Barber (2000).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The lack of backscatter from the melt pond surfaces compared to the sea ice could potentially be used for f MP retrieval utilising σ 0 , as the backscatter intensity becomes weaker with increasing f MP . This is confirmed by Han et al (2016), suggesting σ 0 to be a key feature in f MP estimation for MYI in X-band during calm winds. On the other hand, our results deviate from findings in C-band, where no correlation was found between σ 0 HH and f MP at low wind speeds (U 10 = 1.5 m s −1 ) by Yackel and Barber (2000).…”
Section: Discussionsupporting
confidence: 66%
“…Han et al (2016) found H , α 1 , |ρ|, and ρ to give useful information for f MP retrieval at X-band. …”
Section: Polarimetric Sar Featuresmentioning
confidence: 99%
See 3 more Smart Citations